2022
DOI: 10.1186/s40854-021-00311-8
|View full text |Cite
|
Sign up to set email alerts
|

Energy crypto currencies and leading U.S. energy stock prices: are Fibonacci retracements profitable?

Abstract: This paper investigates the role of Fibonacci retracements levels, a popular technical analysis indicator, in predicting stock prices of leading U.S. energy companies and energy cryptocurrencies. The study methodology focuses on applying Fibonacci retracements as a system compared with the buy-and-hold strategy. Daily crypto and stock prices were obtained from the Standard & Poor's composite 1500 energy index and CoinMarketCap between November 2017 and January 2020. This study also examined if the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Studies like Padhi (2010), Seif et al (2017) and Arora (2017) confirm significant day of the week effects. Other anomalies of EMH have also been evidenced in literature where technical analysis or cross market information have been used for individual security or index movement predictions (Gurrib et al, 2022;Gurrib, 2016;Gurrib, 2018a;Gurrib, 2018b;Gurrib, 2019;Gurrib and Kamalov, 2019).…”
Section: Anomalies Of Emhmentioning
confidence: 87%
“…Studies like Padhi (2010), Seif et al (2017) and Arora (2017) confirm significant day of the week effects. Other anomalies of EMH have also been evidenced in literature where technical analysis or cross market information have been used for individual security or index movement predictions (Gurrib et al, 2022;Gurrib, 2016;Gurrib, 2018a;Gurrib, 2018b;Gurrib, 2019;Gurrib and Kamalov, 2019).…”
Section: Anomalies Of Emhmentioning
confidence: 87%
“…In addition to the strictly financial and legal aspects of these cryptocurrencies, certain studies are focused on the impact that transactions with cryptocurrencies have on sustainable development (by energy consumption, energy transition and electronic waste perspectives), considering the mining process specific to these financial assets. Based on these considerations, certain studies focused the analysis of related risks of conduction mechanism between energy and Bitcoin markets Küfeoğlu and Özkuran, [27]; Li et al [29]; Gurrib et al [23]; Yuan et al [53]. The lack of regulation and supervision accompanied by people's greed have generated numerous frauds that have mainly affected incipient investors, lacking a solid financial culture Maurushat and Halpin, [34]; Savona, [42]; Thakur, [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although numerous trading strategies demonstrated evidence of success in traditional markets including cryptocurrencies, currencies markets, fixed income, and equity markets, uncertainty in financial markets complicates the choice between fundamental analysis and/or technical analysis techniques for investors and traders [19][20][21][22]. It was found that both market conditions and profitability vary over time when applying technical analysis [23].…”
Section: Technical Analysis Based Strategiesmentioning
confidence: 99%